Managing Dryland and Water: A Review of Chapter 4 Soils and Water in the Book Managing Dryland Resources – An Extension Manual for Eastern and Southern Africa - Raodatul Putri; Suwardji (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
Drylands are areas that are vulnerable to environmental degradation due to low rainfall, soil erosion, and limited water resources. The book Managing Dryland Resources – An Extension Manual for Eastern and Southern Africa (IIRR, 2002) presents a variety of practical approaches to managing these challenges. This article reviews Chapter 4: Soils and Water, which focuses on soil and water conservation strategies, pit composting, irrigation and drip irrigation utilization, rainwater harvesting, and sandy river water utilization innovations. The results of the review show that this chapter is strong in presenting field experience and local wisdom combined with modern technology, although it is still limited in quantitative data and socio-economic analysis. These findings confirm that the chapter is relevant as a practical guide for smallholders, extension workers, and stakeholders in sustainable agricultural management in arid regions, both in Africa and in similar regions such as West and East Nusa Tenggara in Indonesia.